2019
DOI: 10.1073/pnas.1910295116
|View full text |Cite
|
Sign up to set email alerts
|

An experimental test of the ovulatory homolog model of female orgasm

Abstract: The ovulatory homolog model of female orgasm posits that the neuro-endocrine mechanisms underlying female orgasm evolved from and are homologous to the mechanisms mediating copulation-induced ovulation in some mammals. This model predicts that pharmacological agents that affect human orgasm, such as fluoxetine, should also affect ovulation in animals with copulation-induced ovulation, such as rabbits. We tested this prediction by treating rabbits with daily doses of fluoxetine for 2 wk and found that fluoxetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…For instance, 14 of the 18 pups of the captive-born females were conceived during the first random mating with males or at any time when they mate. Therefore, we suggest that pangolins may practice copulation-induced ovulation like European rabbits ( Oryctolagus cuniculus ) 23 , 24 , which could be a strategy to enhance their reproductive rate. We also observed that female pangolins could conceive shortly after giving birth or the death of their pups.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 14 of the 18 pups of the captive-born females were conceived during the first random mating with males or at any time when they mate. Therefore, we suggest that pangolins may practice copulation-induced ovulation like European rabbits ( Oryctolagus cuniculus ) 23 , 24 , which could be a strategy to enhance their reproductive rate. We also observed that female pangolins could conceive shortly after giving birth or the death of their pups.…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary explanations have tended to implicitly or explicitly consider the female orgasm as a uniquely human (or, at most, primate) trait. In a series of recent papers, Mihaela Pavličev and Günter Wagner have revised this assumption and revisited the evolutionary enigma of the female orgasm from a comparative scope (Pavličev & Wagner, 2016 ; Wagner & Pavličev, 2017 ; Pavličev et al, 2019 ). Pavličev and Wagner follow Lloyd's critique of adaptationism and bet for “homology thinking” as an alternative explanatory approach to the evolution of the female orgasm (Wagner & Pavličev, 2017 , pp.…”
Section: Back To Phylogenetic Homology: the Ovulatory‐homolog Hypothesismentioning
confidence: 99%
“…Additional difficulty is that a large part of the relevant anatomical literature was published in German (and perhaps other languages), such that a large knowledge base is difficult to access for many researchers. As these and other reasons for the lack of attention to clitoral anatomy are being increasingly overcome in recent decades, we observe intensified research into the details of the female reproductive anatomy, its function and evolution ( Puppo 2013 ; Cunha et al 2014 ; Lima et al 2015 ; Pavlicev and Wagner 2016 ; Sinclair et al 2017 ; Orbach et al 2019 ; Pavlicev et al 2019 ; Levin 2019 ; Orbach et al 2021 ; Brennan et al 2022 ). To further foster this direction of research, we aim at summarizing the comparative anatomical information currently available.…”
Section: Introductionmentioning
confidence: 99%
“…Second, comparative genital anatomy, when combined with other characteristics of mammalian reproduction such as ovarian cycle characteristics and social structure, forms the basis for understanding female genital function and sexuality, as well as their evolution. Our own interest in this area was sparked by the apparent correlation between the nature of the ovarian cycle and genital anatomy, in particular the type of ovulation and the presence of the urogenital sinus (UGS: Pavlicev and Wagner 2016 ; Pavlicev et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%